Cigarette Smoking in Iran - N Zhand; R Ghaletaki; A Meysamie; M Abbasi (Tehran University of Medical Sciences, 2012)
Background: Cigarette smoking is the largest preventable cause of death worldwide. No systematic review is available on the situation of the smoking in Iran, so we decided to provide an overview of the studies in the field of smoking in Iranian populations.Methods: Published Persian-language papers of all types until 2009 indexed in the IranMedex (http://www.iranmedex.com) and Magiran (http://www.magiran.com). Reports of World Health Organization were also searched and optionally employed. The studies concerning passive smoking or presenting the statistically insignificant side effects were excluded. Databases were searched using various combinations of the following terms: cigarette, smoking, smoking cessation, prevalence, history, side effects, and lung cancer by independent reviewers. All the 83 articles concerning the prevalence or side effects of the smoking habit in any Iranian population were selected. The prevalence rate of daily cigarette smoking and the 95% confidence interval as well as smoking health risk associated odds ratio (OR) were retrieved from the articles or calculated.Results: The reported prevalence rates of the included studies, the summary of smoking-related side effects and the ORs (95%CI) of smoking associated risks and the available data on smoking cessation in Iran have been shown in the article.Conclusion: Because of lack of certain data, special studies on local pattern of tobacco use in different districts, about the relationship between tobacco use and other diseases, especially non communicable diseases, and besides extension of smoking cessation strategies, studies on efficacy of these methods seems to be essential in this field.